Enhancing mechanisms of multi-layer graphenes to cementitious composites. (October 2017) - Han, Baoguo; Zheng, Qiaofeng; Sun, Shengwei; Dong, Sufen; Zhang, Liqing; Yu, Xun; Ou, Jinping
Abstract: The mechanical property and underlying enhancing mechanisms of cementitious composites filled with multi-layer graphenes (MLGs) are investigated in this paper. Research results indicate that the addition of MLGs can achieve an enhancement of 54% in compressive strength and a reinforcement of 21% in flexural strength to cementitious composites, respectively. The strengthening effects can be attributed to extensive distribution network of MLGs inside matrix, decreasing ratio of water to cement and self-curing caused by water adsorption and release of MLGs, reducing primary cracks due to MLGs presence, strong bonding between MLGs and matrix, and lowering orientation index of calcium hydroxide crystal in hydration products of cementitious composites. It is therefore concluded that MLGs are effective nanoscale fillers for reinforcing cementitious composites.